The Main Characteristics Of Public Open Online Courses As Educational Technologies - Mallaboyev Nosirjon Murodullayevich; Po’latova Xalimaxon (Zien Journals, 2024)
In this article, the general name of OOOK (MOOC)consists of four separate terms and, analyzing the models for organizing mass open online courses, identified the main characteristics of OOOK that distinguish them from traditional education, as well as other forms of distance learning. The main features of OOOK have been shed light on modern scientific ideas, bringing the continuity and personality-oriented principles of education into a form conducive to implementation, understanding
Keywords: University; Technology; internet; trend